2019
DOI: 10.5935/abc.20190040
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Stiffness: A Predictor of Atrial Fibrillation Recurrence after Radiofrequency Catheter Ablation - A Systematic Review and Meta-Analysis

Abstract: Background Radiofrequency catheter ablation (RFCA) is a standard procedure for patients with atrial fibrillation (AF) not responsive to previous treatments, that has been increasingly considered as a first-line therapy. In this context, perioperative screening for risk factors has become important. A previous study showed that a high left atrial (LA) pressure is associated with AF recurrence after ablation, which may be secondary to a stiff left atrium. Objective To inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
(45 reference statements)
0
13
1
1
Order By: Relevance
“…In a recent study, Reddy et al found that LA Stiff may be the best echocardiographic correlate of elevated filling pressures in patients with preserved LVEF 19 . Finally, abnormal LA Stiff values were associated with an increased incidence of cardiac events 8 and were a strong predictor of atrial fibrillation recurrence 20 . Combining E/Ea and LAS, LA Stiff is strongly influenced by LV properties 21 and is mainly modulated by LV longitudinal function through the downward motion of the mitral plane during ventricular systole.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study, Reddy et al found that LA Stiff may be the best echocardiographic correlate of elevated filling pressures in patients with preserved LVEF 19 . Finally, abnormal LA Stiff values were associated with an increased incidence of cardiac events 8 and were a strong predictor of atrial fibrillation recurrence 20 . Combining E/Ea and LAS, LA Stiff is strongly influenced by LV properties 21 and is mainly modulated by LV longitudinal function through the downward motion of the mitral plane during ventricular systole.…”
Section: Discussionmentioning
confidence: 97%
“…The multicenter observational study LGE‐MRI Determinant of Successful Radiofrequency Catheter Ablation of Atrial Fibrillation (DECAAF) 10 demonstrated that the extent of atrial fibrotic remodeling constitutes the strongest independent predictor of a successful treatment in patients undergoing ablation of AF. Various observational and systematic review studies have further confirmed the predictive value of LA fibrosis on AF ablation outcomes, 11,13‐15 highlighting the need to include atrial myopathy assessment in ablation selection criteria. Additionally, patients with lower residual fibrosis after ablation had less AF recurrence in observational studies, 16 suggesting a potential therapeutic benefit from substrate modification during ablation.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, LA stiffness could be associated with LA histological changes and predicts sinus rhythm maintenance after treatment in AF patients. A systematic review and meta-analysis by Correia et al [ 13 ] found that LA stiffness could be a predictor of AF recurrence after catheter ablation. Indeed, left atrial pressure mirrors the extent of atrial stretch, which promotes both ectopic activity and reentry.…”
Section: Discussionmentioning
confidence: 99%